Social influences in the experience of transition to or from long-term (chronic) pain: A systematic review of qualitative research studies - Samantha Stone; Elaine Wainwright; Amber Guest; Cara Ghiglieri; Anica Zeyen; Rachael Gooberman-Hill (PLoS ONE, 2025)
Background Globally, around 30% of people live with long-term (‘chronic’) pain, with known impact on wellbeing, economic and social lives. Despite increasing attention to contextual and psychosocial aspects of pain, there remains need to understand interrelationships between social phenomena and pain, particularly how social phenomena relate to transitions into and out of chronic pain. Objectives This study aimed to understand how pain experiences relate to social phenomena. We conducted a systematic review and synthesis of qualitative studies that explored social aspects of adults’ experience of chronic pain relating to any condition. Eligibility criteria Studies using empirical qualitative methods, focused on adult experiences of chronic pain, and published after 1979. Data sources Eight electronic databases were searched from 1979 to February 2025: EMBASE; PsycINFO; PubMed; CINAHL; Business Source Complete; Web of Science (including Social Sciences Citation Index); Scopus; Sociological Abstracts. Method The review used a thematic synthesis approach. Searches identified relevant qualitative studies; quality assessment were undertaken using the Critical Appraisal Skills Programme qualitative studies checklist. Material from relevant literature was extracted, coded and thematically grouped. Double processes were undertaken for rigour. Results Analysis of 71 articles, relating to experience of 1,291 people, enabled development of three themes relating to social phenomena and pain: (1) Social connections with family friends and wider community; (2) Lifestyle, including household tasks, eating, sleep and participation in social activities; (3) Occupation, workplace relationships and related financial disadvantage. Although elucidating the importance of social worlds, the literature included in the review paid scant attention to transitions to and from chronic pain or any mechanisms that might support such transitions. Conclusion The review suggests that social phenomena influence people’s experience of living with chronic pain in important ways. However, little research has explored how and why these social phenomena combine with and influence of transitions to and from pain. These insights could inform development of interventions, education and training to support care for people with chronic pain. PROSPERO registration number CRD42022337979